2000
DOI: 10.1063/1.126000
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved photoluminescence studies of AlxGa1−xN alloys

Abstract: The optical properties of AlxGa1−xN alloys with x varied from 0 to 0.35 have been investigated by picosecond time-resolved photoluminescence (PL) spectroscopy. Our results revealed that while the PL intensity decreases with an increase of Al content, the low-temperature PL decay lifetime increases with Al content. These results can be understood in terms of the effects of tail states in the density of states due to alloy fluctuation in the AlxGa1−xN alloys. The Al-content dependence of the energy-tail-state di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
81
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(98 citation statements)
references
References 13 publications
15
81
0
2
Order By: Relevance
“…It can be seen that both lifetimes increase on the lower energy shoulder of the PL peak. This is typical band-edge luminescence behavior in which the shorter lifetime of higher-energy carriers is attributed to the additional relaxation channel via thermalization to lower-energy states [15].…”
mentioning
confidence: 99%
“…It can be seen that both lifetimes increase on the lower energy shoulder of the PL peak. This is typical band-edge luminescence behavior in which the shorter lifetime of higher-energy carriers is attributed to the additional relaxation channel via thermalization to lower-energy states [15].…”
mentioning
confidence: 99%
“…14,15 However, these results point out that an increase of potential fluctuations can occur with well thickness as well. Previously, several reports suggested that the localized states may arise from In compositional fluctuation or QD formation, phase separation, monolayer thickness fluctuation, and surface segregation.…”
mentioning
confidence: 48%
“…This situation is unlike the traditional AlGaN alloys. For AlGaN ternary alloys, the near band emission usually gets weaker as the Al content increases [18]. In III-N based materials, the misfit dislocation normally plays the role of nonradiative recombination centers [19], the higher Al content causes larger lattice mismatch between the GaN buffer and AlGaN, leading to a higher number of defects which results in weaker emission intensity [20].…”
Section: Figure 1amentioning
confidence: 99%